Pengaruh Pemberian Ekstrak Buah Pala terhadap Kadar Eritrosit (RBC) dan Granulosit pada Tikus Putih (Rattus norvegicus) dengan Anemia - Hasanah, Uswatun; Pangesti, Ira; Puspodewi, Dini (Jurnal Laboratorium Khatulistiwa, 2025)
Anemia is a condition characterized by a decreased number of erythrocytes and an increased number of leukocytes. According to the 2023 Indonesian Health Survey, the prevalence of anemia across all age groups is 16.2%, with a higher rate in women (18%) compared to men (14.4%). Nutmeg (Myristica fragrans Houtt) contains bioactive compounds such as saponins, flavonoids, alkaloids, and essential fatty acids that may contribute to increasing red blood cell counts and modulating leukocyte levels. This study aimed to determine the effect of nutmeg fruit extract on increasing RBC and reducing granulocyte levels in anemic white rats. A total of 25 male rats (200–350 g) were divided into five treatment groups. Anemia was induced using NaNO₂ at a dose of 1.5 mg/kg BW orally. Nutmeg extract was administered at doses of 200 mg/kg BW, 300 mg/kg BW, and 400 mg/kg BW. There were no significant differences (p > 0.05) between the positive control and treatment groups, nor between pre- and post-extract administration. At doses of 200 and 300 mg/kg BW, RBC percentage reached 20.7%. For granulocytes, the 300 mg/kg BW dose produced a higher percentage (27.6%) compared to the 200 and 400 mg/kg BW doses. These findings suggest that nutmeg fruit extract has the potential to support erythrocyte balance in anemia conditions, although further research with larger samples and controlled dosing is needed.%.